Stabilization in early adult-onset myopia with corneal refractive therapy - González-Méijome, José Manuel (2016)
Purpose: To describe the stabilization of early adult-onset myopia in three university students after initiating orthokeratology treatment with corneal refractive therapy contact lenses. Methods: Three Caucasian early adult-onset progressing myopic subjects (1 male, 2 females) were fitted with corneal refractive therapy lenses to correct myopia between ?1.50 and ?2.50 D of sphere using Paragon CRT (Paragon Vision Sciences, Mesa, AZ)lenses for overnight orthokeratology. The pre-treatment refractive history from 2005 as well as refraction and axial length after treatment onset are reported over a period of 3 years between December 2009 and January 2013 with an additional year of follow-up after treatment discontinuation (January–December 2013). The peripheral refractive patterns and topographic changes are also reported individually. Results: Treatment was successful in all three subjects achieving uncorrected visual acuity of 20/20 or better monocularly. During a period of 3 years of follow-up the subjects did not experience progression in their refractive error, nor in their axial length (measured during the last 2 years of treatment and 1 year after discontinuation). Furthermore, the subjects recovered to their baseline refraction and did not progressed further over the following year after lens wear discontinuation. Conclusions: We cannot attribute a causative effect to the orthokeratology treatment alone as underlying mechanism for myopia stabilization in this 3 patients. However, the present report points to the possibility of stabilization of early adult-onset myopia progression in young adults using corneal refractive therapy treatment.